Characterizing protection ability of blue blocking lenses using k-means clustering - Che Azemin, Mohd Zulfaezal; Ahmad, Norsham; Ithnin, Mohd. Hafidz; Mohd Salleh, Mohd Hazimin; Mohd Tamrin, Mohd Izzuddin; Rosli, Saiful Azlan (Institute of Mechanics of Continua and Mathematical Sciences, 2020)
Blue light protection ophthalmic lenses have been regularly marketed as the ultimate protection against short-wavelength visible radiation mainly in the range of 400 nm and 450 nm. However, the actual protective effects of such lenses are currently unknown; most claims are provided by the manufacturers with limited scientific validation. This will not only make selling such lenses challenging but may provide the lens wearers little or no protection against the blue light hazard. It is recently discovered that the protection needs to take into accounts the light source that the wearers wish to protect from – heavy electronic gadget users for instance, are exposed to different spectrum of radiation compared to non-users. This problem is aggravated when the hazard needs to further be classified into the visual and non-visual effects. Non-visual impact includes the disruption in the circadian cycle which is governed by the physiological cycles of our body within 24 hours such as the melatonin hormone secretion. Such knowledge will help to educate optometrist to explain to their prospective customers and will also assist the spectacle wearers to make an informed decision based on validated scientific data.